Analisis Pengaruh Ketimpangan Pendapatan Dan Upah Minimum Regional Terhadap Kemiskinan Di Sumatera Utara - Dongoran, Faisal R.; Sulfina, Sri Dai; Syah, Syamsul Allim; Siahaan, Triana (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2022)
Poverty is a problem that cannot be separated from problems that exist in every country and in the world. In this research, it examines income inequality, regional minimum wages for the level of poor people in North Sumatra Province in 2010-2019. The objectives This research is to find out and analyze how income inequality and regional minimum wages affect the level of poor people in North Sumatra Province in 2010-2019. This study uses secondary data from the Central Bureau of Statistics for North Sumatra Province for the 2010-2019 observation.. And the data analysis method used in this research is multiple linear regression analysis using eviews 10.